Interpersonal Communication of Students and Lecturers in Thesis Guidance - Mailani, Desi; Edison, Edison; Diani, Rahma (Social Sciences and Humanities Reviews, 2025)
Background: The thesis guidance process requires effective interpersonal communication between students and supervisors so that the final project can be completed properly. However, in practice, obstacles are often found that interfere with the smooth flow of communication. Aims: This study aims to determine the dynamics of interpersonal communication between Communication Science students and supervisors in the process of making a thesis at UIN Suska Riau, as well as identify obstacles and solutions that occur during guidance. Methods: This study uses a qualitative method with a phenomenological approach. Data were collected through in-depth interviews with 7 students and 4 supervisors, then analyzed using Colaizzi's phenomenological analysis technique. Results: Results show that interpersonal communication takes many forms, especially through digital media such as WhatsApp and Zoom. Obstacles found include delayed responses, lack of openness, and miscommunication. Aspects of openness, empathy, support, positive attitudes, and equality influence the success of mentorship. Conclusion: Effective interpersonal communication contributes significantly to the smooth preparation of thesis. Therefore, both lecturers and students need to build relationships that are open, supportive, and respectful of each other.